Penyakit Ginjal Polikistik disertai Anemia Hemolitik Autoimun - Yossa Tamia Marisa; Harnavi Harun (Universitas Wijaya Kusuma Surabaya, 2021)
The hereditary forms of polycystic kidney disease of autosomal dominant PKD (ADPKD) and autosomal recessive PKD (ARPKD) are the main forms. ADPKD is a multifactorial disorder characterized by bilateral renal cysts and commonly affects adult patients. The most common extrarenal manifestations of ADPKD are liver cysts and is often incidental findings and clinically insignificant. A case report has been reported with polycystic disease in the kidneys and liver with autoimmune hemolytic anemia. ADPKD is a progressive disease and symptoms tend to get worse over time. ADPKD involves managing the symptoms and slowing disease progression. The most serious complication of ADPKD is end stage kidney failure. This aim of this study were to determine the symptoms and laboratory tests that confirm the diagnosis of polycystic kidney disease accompanied by autoimmune hemolytic anemia.